1979
DOI: 10.1111/j.1365-3083.1979.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Senile Cardiac Amyloidosis: Evidence of Two Different Amyloid Substances in the Ageing Heart

Abstract: Lymphocytes were eluted from the synovial tissue of seventeen patients with rheumatoid arthritis (RA) and one with ankylosing spondylitis. In eight of these patients immunoglobulin production by synovial lymphocytes in the presence and absence of pokeweed mitogen was studied. In nine patients T lymphocytes were isolated from the eluted cells, and the T helper and suppressor cell functions were evaluated in an allogeneic co-culture system. Peripheral blood lymphocytes (PBL) from twenty-eight normal donors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This discrepancy is unlikely to be related to the type ofamyloid. It was recently found that cardiac senile amyloidosis (Westermark et al, 1979), the hereditary amyloid heart disease described by Frederiksen et al (1962), and hereditary polyneuropathic amyloidosis (Olofsson, 1982;Eriksson, 1984) all with marked cardiac impairment are, like AFp, related to prealbumin. David et al (1984) studied the hearts of 11 patients with amyloidosis, 4 of which had AFp, 5 reactive amyloidosis and 2 myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is unlikely to be related to the type ofamyloid. It was recently found that cardiac senile amyloidosis (Westermark et al, 1979), the hereditary amyloid heart disease described by Frederiksen et al (1962), and hereditary polyneuropathic amyloidosis (Olofsson, 1982;Eriksson, 1984) all with marked cardiac impairment are, like AFp, related to prealbumin. David et al (1984) studied the hearts of 11 patients with amyloidosis, 4 of which had AFp, 5 reactive amyloidosis and 2 myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Chattopadhyay et al reported that most of the normal donors had suppressor cell activity in their peripheral blood, whereas a statistically significant number of patients did not have any suppressor cell activity in synovial tissue lymphocytes [125]. …”
Section: Natural Regulatory T Cells and Ramentioning
confidence: 99%
“…IAA is one of the most prevalent types of senile amyloidosis and has been found in about 80% of non-selected necropsy cases over 80 years of age."' 34 The atrial amyloid deposits are usually small and tend to coat muscle cells. On electron microscopy, a close relation between the amyloid fibrils and cell membranes of muscle cells is seen, and apparent intracellular amyloid fibrils have been identified.…”
Section: Physiology Of Iappmentioning
confidence: 99%